2013
DOI: 10.1371/journal.pone.0079274
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Ras2-GTP Controls Invasive Growth in Saccharomyces cerevisiae

Abstract: Using an eGFP-RBD3 probe, which specifically binds Ras-GTP, we recently showed that the fluorescent probe was localized to the plasma membrane and to the nucleus in wild type cells growing exponentially on glucose medium, indicating the presence of active Ras in these cellular compartments. To investigate the nuclear function of Ras-GTP, we generated a strain where Ras2 is fused to the nuclear export signal (NES) from the HIV virus, in order to exclude this protein from the nucleus. Our results show that nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These observations, and the fact that the uptake of glucose is not impaired by alkalinization of the medium 56 , could indicate that the impact of alkaline pH on the PKA pathway occurs in response to alteration of intracellular glucose metabolism and not to defects in the transport process and/or extracellular glucose detection. Recently, Broggi and coworkers 71 showed that high pH stress affects localization of Ras2, which becomes transiently excluded from the nucleus and translocates to the plasma membrane, and that the treatment triggers a fast increase in the Ras2-GTP/total Ras2 ratio. The authors postulate that alkalinization down-regulates the cAMP/PKA pathway acting on element(s) downstream Ras and that the increase of Ras2-GTP might be explained by a decrease of the reported feedback inhibition operated by PKA on Ras2 72 .…”
Section: Introductionmentioning
confidence: 99%
“…These observations, and the fact that the uptake of glucose is not impaired by alkalinization of the medium 56 , could indicate that the impact of alkaline pH on the PKA pathway occurs in response to alteration of intracellular glucose metabolism and not to defects in the transport process and/or extracellular glucose detection. Recently, Broggi and coworkers 71 showed that high pH stress affects localization of Ras2, which becomes transiently excluded from the nucleus and translocates to the plasma membrane, and that the treatment triggers a fast increase in the Ras2-GTP/total Ras2 ratio. The authors postulate that alkalinization down-regulates the cAMP/PKA pathway acting on element(s) downstream Ras and that the increase of Ras2-GTP might be explained by a decrease of the reported feedback inhibition operated by PKA on Ras2 72 .…”
Section: Introductionmentioning
confidence: 99%
“…This data is consistent with a model in which both yeast Ras1 (Figure 2 ) and the HOG osmosensors (Tanigawa et al, 2012 ) are activated by an osmotically-induced laterally segregation into spatially distinct plasma membrane nanoclusters, with a cross-talk between them occurring at downstream effectors (Gutin et al, 2015 ). On the other hand, Ras2 appears to be present mainly at endomembranes, a conclusion that is supported by the findings that Ras2 and its effectors are localized in the ER and mitochondrial membranes (Belotti et al, 2012 ) as well as in the nucleus of cells growing exponentially on glucose medium (Broggi et al, 2013 ).…”
Section: The Cross-talk Between the Hog And The Ras Pathwaysmentioning
confidence: 74%
“…This appears to be consistent with the interaction between HCA and the signalling pathways of RAS2 or SCH9. Indeed, in optimal growth conditions, the loss of either gene poorly affects µ [43,44], while these regulators are important for cell responses during physiological transitions, in particular involving nutrients, cellular quiescence or oxidative stresses [9,[44][45][46][47]. Consequently, HCA effects on metabolism were more directly investigated by measuring the oxygen consumption rate (OCR) of stationary phase cells, just before they started to age (day 0 CLS, see above) (Fig.…”
Section: Hca Could Control Yeast Growth As a Function Of Cell Physiology And Inhibited Respirationmentioning
confidence: 99%